ANTIPYRETIC TEST OF BOILED WATER OF MANGOSTEEN PEEL - Christianto Adhy Nugroho (Program Studi Biologi - Universitas Katolik Widya Mandala Surabaya (kampus Kota Madiun), 2018)
Health is one of the most important aspects of human life. The use ofmedicinal plant was one effort to maintain human health. The study was focused on the study of boiled water of magosteen peel as an antipyretic. The study was used three treatment and three replication. The study used mice as animal test. Group I would be used control without treatment, group II woud be used as treatment of 200 g of boiled water of mangosteen peel as much as 0,5 ml/mice, group III would be used as treatment of 300 g of boiled water of mangosteen peel as much as 0,5 ml/mice. All mice would be undergo fever injection using DPT vaccine. The result showed that boiled water of mangosteen peel doesn’t have a function as antipyretic.